Patient absenteeism in outpatient consultations: an integrative literature review - Baptista, Simone Cristina Paixão Dias [UNESP] (2021)
Objective: To identify and analyze the production of knowledge in national andinternational literature on patient absenteeism in scheduled medical consultations.Method: This is an integrative literature review in the databases PubMed, Embase,Scopus, Web of Science, CINAHL, Medline, LILACS, Virtual Health Library of theSão Paulo State Department of Health and Spanish Bibliographic Index in HealthSciences, accessed through the Virtual Health Library Portal, based on the guidingquestion. Results: A total of 767 articles was found and nine were selected. Forgetfulnesspredominated among the reasons for absence. Other findings regarding the cost tothe health service and strategies for solving the problem are highlighted. Conclusion:As the focus of the studies, the concern with the quality of care, increased treatmentqueues and high demand, as well as the cost of absent patients, are evident. Despite therelevance of the theme for the health services organization, the literature is still scarce.